1985
DOI: 10.1084/jem.161.6.1525
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical similarities between monoclonal antibacterial Waldenstrom's macroglobulins and monoclonal anti-DNA lupus autoantibodies.

Abstract: Six monoclonal IgM from patients with Waldenstrom's macroglobulinemia that react with Klebsiella polysaccharides were tested for their ability to bind to nucleic acid antigens. One of the macroglobulins bound to the polynucleotide poly(G), and one bound to poly(G), poly(I), and single-stranded DNA. The reaction with the polynucleotides was specifically inhibited by the Klebsiella polysaccharide K30. A monoclonal lupus anti-DNA antibody (16/6) was found to react weakly with the Klebsiella polysaccharides K30 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Indeed, anti-DNA has now been linked to infec tion with bacteria [11][12][13], mycobacteria [14], viruses [15,16], as well as parasites in mice, rabbits, and man [17][18][19], Whether any of these infections contribute directly to SLE has not yet been determined, although a causal role of in fection in SLE would suggest that lupus is mechanistically similar to other autoimmune dieseases where foreign anti gens are clearly provocative. Further studies on the struc tural properties of anti-DNA antibodies arising in lupus and infection are in progress and should clarify these etiological relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, anti-DNA has now been linked to infec tion with bacteria [11][12][13], mycobacteria [14], viruses [15,16], as well as parasites in mice, rabbits, and man [17][18][19], Whether any of these infections contribute directly to SLE has not yet been determined, although a causal role of in fection in SLE would suggest that lupus is mechanistically similar to other autoimmune dieseases where foreign anti gens are clearly provocative. Further studies on the struc tural properties of anti-DNA antibodies arising in lupus and infection are in progress and should clarify these etiological relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Idiotypic studies have demonstrated a relationship between autoantibodies and antibodies against foreign antigen (1)(2)(3)(4). These studies have led to the hypothesis that there is a genetic relationship between autoantibodies and antibodies to foreign antigens, with the same immunoglobulin variable region genes encoding both pathogenic and protective antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Naparstek et al [18] found a double specificity of antibodies, which react with both autoantigens and bacterial antigens. Thus, some Waldenstrom macroglobulins with anU-Klebsiella ac tivity share idiotypic determinants with the lupus anti-DNA autoantibody and also bound to nucleic acid antigens.…”
Section: Discussionmentioning
confidence: 99%